Evaluation of the Lip-Tooth Relation in Various Growth Patterns- A Cephalometric Study - Akriti Tiwari1 , Ravindra Kumar Jain2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Upper incisor crown exposure is directly influenced by hard and soft tissue structures that surround andsupport these teeth. The amount of upper incisor crown exposure has a direct impact on dentofacial esthetics.Lip-tooth relationship during speech and smiling are important aspects of facial esthetics. Hence, the aimof this study was to evaluate the lip-tooth relations in subjects with different types of growth patterns usinglateral cephalograms. Methods-This was a retrospective study wherein case records of adult subjects aged18-35 years were involved. A total of 30 case records of patients who had reported to a university hospitalwere identified and included in the study. The records of subjects were divided equally into three groupsGroup A - horizontal growth pattern; group B - average growth pattern and group C - vertical growth pattern.All lateral cephalograms were measured using FACAD software. A chi-square test was used to determinethe association of lip-tooth relationships in various growth patterns. One-way ANOVA was used to comparethe incisor exposure in different growth patterns. One-way ANOVA reported a statistically significantdifference in lip-tooth exposure in various growth patterns (p=0, p<0.05). Similarly, chi-square test revealeda statistically significant association between lip-tooth relationships in various growth patterns (p=.00,p<0.05) Within the limitations of this study it can be concluded that there was an increased cervico-incisalexposure of incisors in vertical growth pattern as compared to average and horizontal growth patterns.